Perceived sexual harassment at work: meta-analysis and structural model of antecedents and consequences - Topa Cantisano, Gabriela; Morales Domínguez, J. F.; Depolo, Marco (The Spanish Journal of Psychology, 2008)
Although sexual harassment has been extensively studied, empirical research has not led to firm conclusions about its antecedents and consequences, both at the personal and organizational level. An extensive literature search yielded 42 empirical studies with 60 samples. The matrix correlation obtained through meta-analytic techniques was used to test a structural equation model. Results supported the hypotheses regarding organizational environmental factors as main predictors of harassment.